2022
DOI: 10.3390/agriculture12030365
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Yield and Photosynthetic Characteristics of Two Corn (Zea mays L.) Hybrids Differing in Maturity under Different Irrigation Treatments

Abstract: Effective irrigation strategies are of great significance for improving crop yields. There is an increasing concern that short-season corn hybrids are gradually being encouraged to plant in the North China Plain (NCP) with the development of mechanized grain harvesting, but the photosynthetic characteristics and productivity of short-season hybrids are not well documented. The objective of the study was to investigate the effects of different irrigation treatments on photosynthetic characteristics, dry matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
1
5
0
1
Order By: Relevance
“…Algo semejante se observó en la variable RFS, en el que, la combinación sistema de riego por goteo subsuperficial -100% de evaporación fue superior a las demás (p< 0.05), con 14.85 t ha -1 y el rendimiento más bajo se obtuvo en el sistema de riego superficial -50% de evaporación con 8.67 t ha -1 (Cuadro 1). Valores similares fueron reportados por Yescas et al (2015); Wang et al (2022) quienes mencionan que los valores más altos de RFS se obtuvieron en el tratamiento con lámina de riego correspondiente al 100% de la evapotranspiración diaria con 14.78 t ha -1 y que el RFS en el sistema de riego por goteo, fue 16.24% superior al del sistema de riego por inundación.…”
Section: Resultados Y Discusiónunclassified
“…Algo semejante se observó en la variable RFS, en el que, la combinación sistema de riego por goteo subsuperficial -100% de evaporación fue superior a las demás (p< 0.05), con 14.85 t ha -1 y el rendimiento más bajo se obtuvo en el sistema de riego superficial -50% de evaporación con 8.67 t ha -1 (Cuadro 1). Valores similares fueron reportados por Yescas et al (2015); Wang et al (2022) quienes mencionan que los valores más altos de RFS se obtuvieron en el tratamiento con lámina de riego correspondiente al 100% de la evapotranspiración diaria con 14.78 t ha -1 y que el RFS en el sistema de riego por goteo, fue 16.24% superior al del sistema de riego por inundación.…”
Section: Resultados Y Discusiónunclassified
“…Anjum et al (2018)and Li et al (2020) also reported a change in days to tasseling of maize with different bulk densities of soil. Wang et al (2022) also reported a negative correlation between hybrid maize yield with the increase in soil compactness. This could be because roots need to take up more nutrients for the plant, which were restricted by soil with high compaction due to higher bulk densities.…”
Section: Discussionmentioning
confidence: 92%
“…Hybrids did not differ for E/ET during the whole growing season, but E/ET was higher in EM than in LM during the R3–R6 stage. The phenomenon was associated with the rapid advance of the leaf senescence process for EM hybrid during the R3–R6 stage, resulting in higher soil E via the reduction in percent ground cover (L. Wang et al., 2022). Soil E in maize constituted a similar proportion (almost 40%–55%) of total ET each season.…”
Section: Resultsmentioning
confidence: 99%